(3ChbGJ efSjIs (3QhGjIs - (3GdLed, eMeOs; (3YHO GdhGMO, UHQis ((3GdbGgQIs (3GdgjFI GdeUQjI GdYGeI ddcJGHs, 2001)
(3TGAJ GdCbOGQ Cf jUHM SQMGf SQMGf (B((3HWd GdQhGjI(B) (3VMjI UQGY eQjQ Ydi GdYehOjI, ai bQjJg (B((3GdeQGZI(B)(3, ai UHGg GdHGcQ, MjK Je GZJUGH GdYehOjI ef CHjg, GdPi dabJ dg JgeI cGPHI, CONdJg GdSLf heGJ ajg(B. (3hjVWQ (B_ (3HSHH edGMbI GdYeOI dg hGaJbGO GdMeGjI (B_ (3Edi GdgQH ahb SWM bWGQ, MjK jLO faSg HGdEScfOQjI, jhGUd GdMjGI JMJ CUYH hCbUi GdXQha(B. (3hYfOeG bQQ GSJOYGA Ceg ddYjT eYg, Yde CfgG gQHJ ef GdeQGZI, hgi JMed LfjfgG ai HWfgG, dJfLh ef HWT hNSI GdYeOI, GdPi cGf eMd JbOjQ Cgd GdbQjI (B.(3hjfLM SQMGf (B_ (3hSW GdeUGYH (B_ (3ai GSJceGd JYdjeg, hGdYed HGdJOQjS, hGdRhGL hGdEfLGH, Ke JMOK aJQI JhJQ GLJeGYi MGO, JJUGYO hJjQJgG, aJDOi Hg Edi GdSLf , hjaQL Yfg eY ZjQg, HaVd eMGejg bOjQI,jcJTa CfgG CNJg, GdJi cGfJ LfjfkG ai HWf Ceg hbJ gQHg ef bQjJg(B. (3hjhGUd SQMGf hCNJg , eY ZjQge, QMd GdcaGM dfTOGf GdeOjfI GdaGVdI, ef NdGd cTa GdefMQajf hGdGfJgGRjjf hGdCTQGQs
11
Keywords: (3GdbUU GdYQHjIs -- (3eUQs; (3GdbUU GdYQHjIs